Feasibility Study of a Grid Connected Hybrid Wind/PV System - Hussein AL-Masri; Fathi Amoura (International Journal of Applied Power Engineering (IJAPE), 2013)
This paper investigates the feasibility of a grid connected, large-scale hybrid wind/PV system. From data available an area called RasElnaqab in Jordan is chosen because it enjoys both high average wind speed of 6.13 m/s and high average solar radiation of 5.9KWhr/m2 /day. MATLAB and HOMER software’s are used for sizing and economical analysis respectively. Results show that76124 SUNTECH PV panels and 38 GW87-1.5MW wind turbines are the optimal choice. The net present cost (NPC) is 130,115,936$, the cost of energy (COE) is 0.049$/KWhr with a renewable fraction of 74.1%.A stepby-step process to determine the optimal sizing of Hybrid Wind/PV system is presented and it can be applied anywhere.